The resolution of the transition conflict from tourism to mining in Pangkal Niur Village through the strengthening of social capital - Herdiyanti, Herdiyanti; Sarpin, Sarpin; Sulaiman, Aimie (Faculty of Social and Political Science, Universitas Airlangga, 2023)
Utilization of social capital is considered capable of addressing conflicts that arise in rural areas, especially those related to tourist areas that are part of community empowerment programs. This study examines the crucial role of social capital in dealing with conflicts arising from the transition from the tourism sector to mining in Pangkal Niur Village. This study used qualitative methods. The analysis results depict in-depth how social capital significantly mitigates conflicts between the tourism and mining sectors. The implications of this social capital are also highlighted in the context of modernization and globalization, especially concerning the local community in Pangkal Niur Village. Additionally, this research emphasizes the importance of social relationships in forming the basis of trust, cooperation, and community participation. In the context of post-mining land restoration efforts, sustainable actions are crucial to reduce environmental damage caused by such functional changes, especially in regions with significant mining sectors like Bangka Belitung. The findings of this research have broad implications, especially in environmental management and sustainable development. The study concludes that social capital can play a role in resolving conflicts, but continuous efforts are still needed to preserve the environment and enhance community well-being.